2016
DOI: 10.4067/s0718-95162016005000081
|View full text |Cite
|
Sign up to set email alerts
|

Organic acid coated-slow-release phosphorus fertilizers improve P availability and maize growth in a tropical soil

Abstract: In this paper, we report the results of studies on the solubility (water solubility trial) and the response by plants (greenhouse pot experiment using Zea mays) for four types of monoammonium phosphate fertilizers (Conventional MAP -MAP 1 , MAP coated with a natural organic acid -MAP 2 , MAP coated with a synthetic organic acid -MAP 3 , and MAP coated with a peat humic organic acid -MAP 4 ) applied at five increasing doses (0, 100, 300, 600 and 1200 mg P dm -3 ) and pre-incubated with the soil for five lengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Coating, allowing a release of P that follows flow and diffusion mechanisms, induces a slow P release (Shaviv and Mikkelsen, 1993;Du et al, 2006), as found in our study when coated and uncoated MAP were compared. The gradual P solubilisation from PCMAP can provide a more constant P supply toward the soil where roots are developing thus enabling greater efficiency as also reported by other authors (Pauly et al, 2002;Sanders et al, 2012;Teixeira et al, 2016). In fact, the higher the coating, the lower the P availability Olsen,water) and the higher the plant LGC, DW, and P uptake were.…”
Section: Soil Extractable P and Plant Growthsupporting
confidence: 65%
See 2 more Smart Citations
“…Coating, allowing a release of P that follows flow and diffusion mechanisms, induces a slow P release (Shaviv and Mikkelsen, 1993;Du et al, 2006), as found in our study when coated and uncoated MAP were compared. The gradual P solubilisation from PCMAP can provide a more constant P supply toward the soil where roots are developing thus enabling greater efficiency as also reported by other authors (Pauly et al, 2002;Sanders et al, 2012;Teixeira et al, 2016). In fact, the higher the coating, the lower the P availability Olsen,water) and the higher the plant LGC, DW, and P uptake were.…”
Section: Soil Extractable P and Plant Growthsupporting
confidence: 65%
“…Considering the treatment, it is noteworthy that SSP and PCMAP showed a lower P release in water than MAP, as evidenced by the clustering of the soil plots at the initial and final section of the segmented-line. Uncoated fertilizers, in fact, had high rate of P release and led to a fast increase of the P concentration in the soil solution (Silva et al, 2012;Teixeira et al, 2016). The slower P release of the coated fertilizer might be a result of physical and chemical barriers, whereas issues such as porosity, thickness and coating layer composition determine the P diffusion from the granule to the soil (Shavit et al, 1997;Du et al, 2006).…”
Section: Soil P Release and Environmental Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering this impact of fertilizers on the total energy used in the production of soybean, one way to reduce energy expenditure during production is to increase the efficiency of crop nutrient use. The increased efficiency of P and K fertilizer used (Teixeira, Silva, Sousa, Mattiello, & Soares, 2016), and of green fertilizers that promote nutrient cycling (Silva, Oliveira, Merloti, & Sá, 2017), and rooting promotion via co-inoculation with Bradyrhizobium and Azospirillum (Ferri, Braccini, Anghinoni, & Pereira, 2017) are examples of techniques that have been indicated to increase the efficiency of P and K use by soybean and thereby to increase EE. However, in terms of energy, one should be careful if opting to replace synthetic fertilizers by other sources of these elements.…”
Section: Resultsmentioning
confidence: 99%
“…However, the disadvantages of organic fertilizers were low stability and low nutrient, it could be beneficial when used in an appropriate amount. New technologies to improve fertilizer quality and protect the environments are being developed by such methods as encapsulating the fertilizer by graphene (Zhang et al, 2014), coating them with inorganic materials (Tian et al, 2017;Teixeira et al, 2016;Wu et al, 2008) and/or adsorping them into Zeolite or Silica (SiO2) (Notario del Pino et al, 1995;Cui et al, 2015). These would make controlled-release fertilizer.…”
Section: Introductionmentioning
confidence: 99%